Thinking about fascism since Walter Benjamin [Pensando el fascismo desde walter benjamin] (2020)
The purpose of this article is to present some of the most significant traits of the method used by Walter Benjamin to produce his own critical view about fascist violence within the framework of a historical situation -The post First World War period- in which the future of both German and European society was at stake. To this end, some premonitions warning about the risks of War and Militarism raised in his essays are explored, as well as his concern about social indifference in the face of negative values through which the Aesthetics of Fascism aimed to alienate the masses by means of diverse kinds of communicational and ethical artifice, but which concealed a retrograde pretension to political control and the destruction of material culture. © 2020 Universita di Trieste. All rights reserved.